2017
DOI: 10.1016/j.cya.2017.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis categorization of EU countries in the context of corporate income tax

Abstract: The corporate income tax is a corporate tax which aggregates economic, political and social aspects. The paper focuses on identification, analysis and assessment of homogenous EU countries groups, which show the common characteristics in the field of corporate taxation based on the selected segmentation criteria. Within the statistical meta-analysis in this paper some several methodical approaches were used: variants of agglomerative hierarchical cluster analysis, k-means method and fuzzy c-means and also mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…As one of the goals of the countries' tax strategy is perhaps attracting foreign investment to increase the tax revenues (Clausing, 2007), and once there is a tendency of countries to decrease the tax rate, several authors investigated the relationship between the nominal tax rate and foreign investment. Alena et al (2017) confirmed "that between countries there are still significant differences in the level of nominal and effective corporate tax burden, especially among a group of old and new EU Member States." Bénassy-Quéré et al (2000) concluded that foreign investment is sensitive to differences in tax rates.…”
Section: Nominal Ratementioning
confidence: 94%
“…As one of the goals of the countries' tax strategy is perhaps attracting foreign investment to increase the tax revenues (Clausing, 2007), and once there is a tendency of countries to decrease the tax rate, several authors investigated the relationship between the nominal tax rate and foreign investment. Alena et al (2017) confirmed "that between countries there are still significant differences in the level of nominal and effective corporate tax burden, especially among a group of old and new EU Member States." Bénassy-Quéré et al (2000) concluded that foreign investment is sensitive to differences in tax rates.…”
Section: Nominal Ratementioning
confidence: 94%
“…The majority of the clustering algorithms are based on two popular techniques known as hierarchical and partitional clustering [41][42][43]. In the present research, two clustering methods were used: hierarchical clustering and k-means clustering.…”
Section: Methodsmentioning
confidence: 99%
“…Once all the parameters are obtained, a categorization is carried out using an unsupervised model known as c-means [37,38]. This model is widely recognized for generating accurate categorizations in comparative studies due to its fuzzy characteristics in categorization, which extends the concept of unsupervised artificial intelligence [39][40][41]. The c-means classification method was implemented in Python, specifically making use of the fuzzy-c-means library [42].…”
Section: Non-supervized Fuzzy Categorizationmentioning
confidence: 99%